Protective Effect of Intestinal Helminthiasis Against Tuberculosis Progression Is Abrogated by Intermittent Food Deprivation - Garrido-Amaro, Cristina; Cardona, Paula; Gassó, Diana; Arias, Lilibeth; Velarde, Roser; Tvarijonativiciute, Asta; Serrano, Emmanuel; Cardona, Pere-Joan (Frontiers in Immunology, 2021)
Background. Tuberculosis (TB) is still a major challenge for humankind. Because regions with the highest incidence also have a high prevalence of helminthiasis and nutritional scarcity, we wanted to understand the impact of these on TB progression. Methods. We have developed an experimental murine model for active TB in C3HeB/FeJ, coinfected with Trichuris muris and Heligmosomoides polygyrus nematodes, and exposed to an environmental mycobacterium (M. manresensis) and intermittent fasting. Cause-effect relationships among these factors were explored with Partial Least Squares Path modelling (PLSPM). Results. Previous parasitization had a major anti-inflammatory effect and reduced systemic levels of ADA, haptoglobin, local pulmonary levels of IL-1β, IL-6, TNF-α, CXCL-1, CXCL-5 and IL-10. Oral administration of heat-killed M. manresensis resulted in a similar outcome. Both interventions diminished pulmonary pathology and bacillary load, but intermittent food deprivation reduced this protective effect increasing stress and inflammation. The PLSPM revealed nematodes might have protective effects against TB progression. Conclusions. Significantly higher cortisol levels in food-deprivation groups showed it is a stressful condition, which might explain its deleterious effect. This highlights the impact of food security on TB eradication policies and the need to prioritize food supply over deworming activities.